PEMBERDAYAAN EKONOMI IBU-IBU PKK DESA MUNGGU MELALUI INOVASI MAKANAN TRADISIONAL - Ayu, Putu Cita; Yuliantari, Ni Putu Yeni; Hutnaleontina, Putu Nuniek; Kusumawati, Ni Putu Ayu; Pramuki, Ni Made Wisni Arie (JURNAL SEWAKA BHAKTI, 2024)
Women’s empowerment in the economic sector is one indicator of improving welfare. The problems that occurred with the PKK partners in Munggu Village were a challenge for the service team to overcome their low entrepreneurial spirit or motivation. Where the women who are members of the PKK team have an interest in entrepreneurship by innovating traditional food, namely pes;an tlengis which is a traditional food made from coconut and various spices which will be made in various flavors, but the partners do not yet understand how to calculate the selling price and still confused about marketing the product. The aim of this service activity is to provide outreach regarding product innovation, training and creating an online marketing platform on social media. The method used is the classical method with a discussion/question and answer approach with the aim that the material can be well received by the participants. The results of this community service activity are increasing the creativity of Munggu Village PKK women in carrying out product innovations, being able to calculate the selling price well and marketing the tlengis products produced, so that this will have an impact on increasing income.